Innate Immunomodulation in Food Animals: Evidence for Trained Immunity? - Byrne, Kristen A.; Loving, Crystal L.; McGill, Jodi L. (Frontiers in Immunology, 2020)
Antimicrobial resistance (AMR) is a significant problem in health care, animal health, and food safety. To limit AMR, there is a need for alternatives to antibiotics to enhance disease resistance and support judicious antibiotic usage in animals and humans. Immunomodulation is a promising strategy to enhance disease resistance without antibiotics in food animals. One rapidly evolving field of immunomodulation is innate memory in which innate immune cells undergo epigenetic changes and chromatin remodeling, and metabolic reprogramming upon a priming event that results in either enhanced or suppressed responsiveness to secondary stimuli (training or tolerance, respectively). Exposure to live agents such as bacille Calmette Guerin (BCG) or microbe-derived products such as LPS or yeast cell wall ß-glucans can reprogram or ‘train’ the innate immune system. Over the last decade, significant advancements increased our understanding of innate training in humans and rodent models, and strategies are being developed to specifically target or regulate innate memory. In veterinary species, the concept of enhancing the innate immune system is not new; however, there are few available studies which have purposefully investigated innate training as it has been defined in human literature. The development of targeted approaches to engage innate training in food animals, with the practical goal of enhancing the capacity to limit disease without the use of antibiotics, is an area which deserves attention. In this review, we provide an overview of innate immunomodulation and memory, and the mechanisms which regulate this long-term functional reprogramming in other animals (e.g., humans, rodents). We focus on studies describing innate training, or similar phenomenon (often referred to as heterologous or nonspecific protection), in cattle, sheep, goats, swine, poultry, and fish species; and discuss the potential benefits and shortcomings of engaging innate training for enhancing disease resistance.